Pengaruh Profitabilitas, Likuiditas, Leverage, dan Aktivitas dalam Memprediksi Financial Distress - Dendy Arda Pratama; Erma Setiawati (JUDICIOUS, 2022)
This study aims to obtain empirical evidence of the influence of profitability, liquidity, leverage, and activity in predicting financial distress conditions in industrial sector companies, consumer non-cyclicals, and basic materials listed on the Indonesia Stock Exchange in 2019-2021. The samples used totaled 75 data samples selected using the purposive sampling method. Data analysis techniques use logistic regression analysis with data processing using SPSS version 25.0. The results of the study can be concluded that profitability as measured by return on assets negatively affects the prediction of financial distress. Liquidity as measured by current ratio has no effect on financial distress predictions. Leverage measured by debt to asset ratio has no effect on financial distress predictions. Activity with total asset turnover has no effect on financial distress predictions.